Risk factors for postherpetic neuralgia: a meta-analysis based on demographic, clinical features, and treatment characteristics - Wang, Jing; Tao, Rong; Jiang, Yinghai; Ma, Zhuoya; Xia, Lingjie (Frontiers in Immunology, 2025)
BackgroundThis study aims to comprehensively analyze the independent risk factors of postherpetic neuralgia (PHN) through a systematic evaluation, including demographic characteristics, clinical manifestations, treatment regimens, comorbidities, and virological factors, in order to provide evidence-based support for the early identification of high-risk patients and the optimization of preventive strategies in clinical practice.MethodA systematic search of PubMed, Embase, and the Cochrane Library was conducted to identify studies reporting risk factors for PHN. After screening the literature according to predefined inclusion and exclusion criteria, effect size indicators such as odds ratios (OR) and 95% confidence intervals (95% CI) for each risk factor were extracted. Meta-analyses were performed using RevMan 5.4 and Stata 15.0 software, with a random-effects model applied to pool effect sizes. Publication bias was assessed using Egger’s test, and sensitivity analysis was conducted by sequentially removing individual studies to verify the robustness of the result.ResultsAge (≥60 years), severe rash manifestations, prodromal pain symptoms, smoking history, alcohol abuse, immunosuppressive status, and comorbidities including diabetes mellitus, chronic obstructive pulmonary disease (COPD), hypertension, malignant tumors, or chronic kidney disease, along with high viral load, have been identified as independent risk factors for the development of PHN(p<0.05). In contrast, gender differences and socioeconomic status were not significantly associated with PHN incidence, with insufficient evidence observed (I²>50%, p>0.05).ConclusionThis meta-analysis confirms that older age (≥60 years), severe rash, prodromal pain, immunosuppressive therapy, and smoking are significant risk factors for PHN. Furthermore, it identifies alcohol abuse, T2DM, COPD, hypertension, cancer, high pain scores (as measured by VAS or NRS), and high HZ viral load as additional risk factors. COVID-19 may represent a potential risk factor that must be further investigated. The association between socioeconomic status and PHN remains inconclusive, while antibody levels against varicella-zoster virus (VZV) may serve as a protective factor.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025629699.